2011
DOI: 10.1016/j.micres.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein acyltransferase function of recombinant purified GlnA1 from Mycobacterium tuberculosis: A moon lighting property

Abstract: The protein acetyltransferase (MTAase) function of glutamine synthetase of Mycobacterium smegmatis was established earlier. In this paper, studies were undertaken to examine MTAase function of recombinant glutamine synthetase (rGlnA1) of Mycobacterium tuberculosis, which showed >80% similarity with M. smegmatis GlnA. The specificity of MTAase to several acyl derivative of coumarins was examined. The results clearly indicated that MTAase exhibited differential specificities to several acyloxycoumarins. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The measured activity of Microbacterium sp. 4N2-2 GS for norfloxacin N-acetylation was not as high as that for glutamine synthesis; neither was it as high as the activities of other N-acetyltransferases (14,36,37), as shown by the K m and V max values. The K m for norfloxacin was similar to the K m for glutamate, but it was more than 10-fold higher than the K m values reported for ATP and NH 4 Cl with the GS of Nocardia asteroides (38).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The measured activity of Microbacterium sp. 4N2-2 GS for norfloxacin N-acetylation was not as high as that for glutamine synthesis; neither was it as high as the activities of other N-acetyltransferases (14,36,37), as shown by the K m and V max values. The K m for norfloxacin was similar to the K m for glutamate, but it was more than 10-fold higher than the K m values reported for ATP and NH 4 Cl with the GS of Nocardia asteroides (38).…”
Section: Discussionmentioning
confidence: 84%
“…A so-called "moon lighting property" of GS in Mycobacterium spp. is the N-acetylation of glutathione S-transferase, with a polyphenolic acetate as an acetyl group donor (36,37). The measured activity of Microbacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Acetyl CoA-independent protein acetylation is also known, but is restricted to the action of aspirin-like drugs that would readily acetylate cyclooxygenase resulting in the inhibition of prostaglandin synthesis and, thus, induce anti-inflammatory effects [14]. Through extensive studies, we identified a microsomal enzyme, protein transacetylase (TAase) in mammalian cells and tissues, catalysing the transfer of acetyl groups from 7,8-diacetoxy-4-methylcoumarin (DAMC) to certain receptor proteins, viz., cytosolic glutathione S-transferase (GST), cytochrome P-450-linked mixed function oxidases (MFO), Nicotinamide Adenine Dinucleotide Phosphate (NADPH) cytochrome c-reductase, protein kinase C (PKC), nitric oxide synthase (NOS), and recombinant glutamine synthetase (rGlnA1) of Mycobacterium tuberculosis, resulting in the modulation of their catalytic activities and associated physiological effects [15][16][17][18][19][20]. The rat liver and human placental microsomal TAase was later identified as calreticulin, a calcium-binding protein in the lumen of the endoplasmic reticulum and, consequently, the acetyltransferase function of calreticulin was appropriately termed calreticulin transacetylase (CRTAase) [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The acetylation of receptor proteins such as GST and NOS at -amino group lysine residues was established by immunoblotting using acetylated lysine antibody and mass spectrometry [6,7]. Recently, TAase was identified and established by us in bacterial species such as Mycobacterium smegmatis [8] and Mycobacterium 2 ISRN Structural Biology tuberculosis (Mtb) H37Rv [9] as glutamine synthetase (GS). Glutamine synthetase catalyzes the conversion of glutamate to glutamine in the presence of ammonium ion with simultaneous hydrolysis of ATP which is used as the energy source and plays an essential role in bacterial nitrogen metabolism [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several PAs, including acetoxycoumarins in general, were found to be the substrates for mycobacterial TAase (MTAase). The specificities of various acetoxycoumarins towards MTAase were determined by their ability to inhibit GST irreversibly, and their kinetic constants ( and max ) were determined [9]. Several inhibitors are known for GS and most of them are analogues of glutamate and replace this substrate in the active site of the enzyme.…”
Section: Introductionmentioning
confidence: 99%